Expansion of the basic knowledge on the inheritance of characters that allow the development of new maize brreeding techniques = Expansión de los conocimientos básicos de la herencia de caracteres que posibiliten desarrollar nuevas técnicas de mejoramiento en maíz - Salerno, Juan Carlos; Kandus, Mariana Virginia; Prada, Arturo; Almorza, David (Sociedad Argentina de Genética, 2024)
In order to increase the efficiency of maize hybrid seed production it is necessary to achieve a high grain yield to reduce production costs. This goal requires an expansion of the basic knowledge of the inheritance of characters in order to develop new breeding techniques to improve experimental materials with hard endosperm (flint). The balanced lethal system allows to study the relative contribution of different chromosome segments to hybrid vigour due to the heterozygosity of certain chromosome segments while the rest of the genome becomes homocygotic through continuous selfing. In this way, these segments can be transferred to inbred lines in order to increase grain yield or tassel size (to increase pollen production). The goal of this study was to transfer a heterotic segment by using a balanced lethal system regulated line (BLS14), through crosses and backcrosses, to S5 flint lines derived from two commercial hybrids, ACA 2000 and Cóndor with closed pedigree, with the objective of increase grain yield or tassel size for pollen production. The analysis of variance (ANOVA) and principal components analysis (PCA) showed a significant improvement in grain yield and tassel size in the S5 flint lines of both commercial hybrids, carrying the heterotic segment of the BLS14 line.